1976
DOI: 10.1177/000992287601500505
|View full text |Cite
|
Sign up to set email alerts
|

How Frequent Is Bacterial Superinfection of the Pharynx in Infectious Mononucleosis?

Abstract: Throat cultures from 133 patients with infectious mononucleosis were compared with cultures from 2,881 patients who were seen during the same period because of pharyngitis. Less than 3 per cent of the cultures from each group contained Group A beta hemolytic streptococci. The inflamed pharynx and necrotic tonsils of infectious mononucleosis are seldom subject to bacterial superinfection, either initially or during the course of the illness. There is no indication for routine use of antibiotics when infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…5 Palatine petechiae are sometimes observed. 3,9,10 Although we have found no past reports that correlate the pathological and radiological fi ndings of infl amed tonsils, we speculate that CT enabled us to fi nd edema, a pseudomembrane, and exudates.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…5 Palatine petechiae are sometimes observed. 3,9,10 Although we have found no past reports that correlate the pathological and radiological fi ndings of infl amed tonsils, we speculate that CT enabled us to fi nd edema, a pseudomembrane, and exudates.…”
Section: Discussionmentioning
confidence: 73%
“…11 In our two cases, α-streptococci were detected in their pharyngeal cultures, but this bacterium is part of the normal fl ora in tonsils. 9 We think that our two cases of pharyngitis were caused by not bacterial super-infection but by the EBV infection. Because our cervical CT fi nding that streaky heterogeneous tonsils with interspersed low attenuation was compatible to a fi nding reported in the literature, it is thought that this radiological fi nding could be a useful hint that IM is a possible diagnosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Henke et al similarly commented that 29% of more than 700 patients up to 25 years old with EBV illness had co-infection with GAS pharyngitis (4). In contrast, Chretien et al reported, from a prospective study of 150 college students with infectious mononucleosis, that only 2.4% showed positive throat cultures for GAS (5). To the best of our knowledge, the rate of co-infection in adolescents remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…The difficulty of differentiating certain clinical forms of IM from diphtheria has been well recognized for decades (Chretien & Esswein, 1976). Making an accurate diagnosis is especially difficult in cases of concurrent diphtheria and IM.…”
Section: Discussionmentioning
confidence: 99%